Waist circumference cut-off points for the diagnosis of abdominal obesity in Colombian population by means of bioimpedance as a reference standard (2014)
Correlation study between diagnostic tests and cut-off points of waist circumference to define abdominal obesity in Colombian population where the reference standard was bioimpedance as a method of estimating visceral fat. Minimum sample size was calculated at 366 patients. A total of 501 patients were admitted in the study. Visceral fat measurement using bioimpedance was defined as high over the 9% mark; from there the cut-off points of the waist circumference for men and women were estimated with a ROC curve. A cut-off point of 89 cm was estimated for women, with a sensitivity of 82.35% and specificity of 78.77% and area under the curve 0.89 (CI: 95%, 0.85-0.92). For men, the cut-off point for waist circumference was estimated in 91 cm, with a sensitivity of 82.03% and specificity of 94.83% and area under the curve of 0.9586 (CI: 95%, 0.93-0.98). As a result of this study, the definition of abdominal obesity is proposed as the cut-off point of the waist circumference greater than or equal to 91 cm for men and greater than or equal to 89 cm for women. This useful measure allows the physician to conveniently classify patients with abdominal obesity and metabolic syndrome. © 2015 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular